2021
DOI: 10.1002/pcr2.10199
|View full text |Cite
|
Sign up to set email alerts
|

Aliphatic polyamides (nylons): Interplay between hydrogen bonds and crystalline structures, polymorphic transitions and crystallization

Abstract: Aliphatic polyamides (nylons) constitute a family of polymers with outstanding properties and multiple applications. Despite the intensive research studies carried out with nylons, there are still multiple unsolved questions concerning crystallization processes, crystalline structures, polymorphic transitions, and crystalline morphologies. Constrains imposed by the strong intermolecular interactions affect the amorphous state, the rigid amorphous phase, the molecular folding, the morphology and obviously the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 88 publications
(95 reference statements)
0
13
0
Order By: Relevance
“…The Brill transition has been widely studied in the polyamide family, ,, and recently, a Brill-like transition has been reported for poly­(octamethylene carbonate) (PC8) and poly­(hexamethylene dithiocarbonate) (PC6-D) . In PC8, Zhao et al reported the convergence, upon heating, of the d 110 = 0.43 nm and d 200 = 0.38 nm, observed at low temperatures (in the denoted α phase), into a single d -spacing at 0.41 nm at ∼42 °C (in the denoted β phase).…”
Section: Introductionmentioning
confidence: 99%
“…The Brill transition has been widely studied in the polyamide family, ,, and recently, a Brill-like transition has been reported for poly­(octamethylene carbonate) (PC8) and poly­(hexamethylene dithiocarbonate) (PC6-D) . In PC8, Zhao et al reported the convergence, upon heating, of the d 110 = 0.43 nm and d 200 = 0.38 nm, observed at low temperatures (in the denoted α phase), into a single d -spacing at 0.41 nm at ∼42 °C (in the denoted β phase).…”
Section: Introductionmentioning
confidence: 99%
“…At present, two possibilities are considered for explaining the existence of two different α-phases: First, a more stable H-sheet structure is induced during the annealing in the PAE38 sample to prevent the chain conformation from changing from all-trans to gauche until 150 °C. Although the all-trans conformation is considered the lowest-energy and most stable conformation in the even–even PAs, the researchers evaluated the presence of an intermediate phase ,, based on the experimental results of PA46 and PA66. Moreover, Li et al have demonstrated that the chain conformation could be affected under stretching, inducing the new crystal phase (denoted α′) in PA46.…”
Section: Resultsmentioning
confidence: 99%
“…Polymers containing aromatic rings are more polarized and these polymers have strong intermolecular forces. Hydrogen bonds between amides in polyamides help to stabilize them [ 38 ].…”
Section: Synthetic Polymersmentioning
confidence: 99%